Fra en sjællandsk landsbydegns notesbog: Kirkerupdegnen Frederik Fæderhofs optegnelser 1728-63 - Pedersen, Karl Peder (Kirkehistoriske Samlinger, 2002)
During the 1730’s the religious life of Copenhagen was marked by a strong and often bitter struggle between members ofthe growing Pietistic movement and the clergymen of the Lutheran state-church. The conflict was intensified by the fact that the new king, Christian 6., sympathized with the Pietists. But he was forced to use all his power and authority to suppress the conflict. Upon this time there lived in Kirkerup, only a few hours’ ride from Copenhagen, a parish clerk called Frederik Faederhof (1693-1766). He followed the fight on the religious scene of the capital with great interest. In 1728 he had begun to make notes in an old, blank notebook and he continued to do so during the period of »Pietistic riots« in Copenhagen. These notes allow us to follow the development of the conflict and to examine the spread of information and ties of alliances. Through his vicar, Frederik Monrad, Frederik Faederhof had close relations to the orthodox clergy in Copenhagen, and he saw the Pietists as a danger to the Lutheran absolutist state. In his notebook Frederik Faederhof wrote about a lot of other things, which gives us an idea of his personal horizon and of his mentality. He had a strong interest in the world around him, and thanks to this we have left some very interesting notes from the pietist-ortodox religious conflict of the 1730’s.